A Multiple Linear Regression Analysis of Tiktok’s Marketing Strategies and E-Commerce Sustainability in Greater Jakarta, Indonesia - Michael Lizar (Universitas Pelita Harapan, 2026)
Indonesia’s rapidly expanding digital economy has positioned TikTok as a dominant force in social commerce. However, empirical evidence regarding the effectiveness of TikTok marketing strategies in supporting sustainable E-commerce performance remains limited. This study examines how TikTok’s marketing strategies influence key dimensions of E-commerce sustainability in JaBoDeTaBek (Jakarta, Bogor, Depok, Tangerang, and Bekasi), Indonesia’s most digitally active metropolitan region. Using survey data from 65 active TikTok users, multiple linear regression analysis was conducted to evaluate the effects of platform usage, content strategy, engagement tactics, and advertising strategy on purchase intention, brand recognition, and customer engagement. The results show that platform usage is the strongest predictor of purchase intention (β = 0.586, p < 0.001; R² = 0.671). Content strategy significantly influences all three outcomes, including purchase intention (β = 0.285, p = 0.022), brand recognition (β = 0.563, p < 0.001), and customer engagement (β = 0.497, p < 0.001). Engagement tactics demonstrate a positive effect on customer engagement but do not significantly predict brand recognition, while advertising strategy shows no significant independent effect across the models. These findings indicate that narrative-driven and algorithm-compatible content plays a more critical role than conventional advertising in shaping consumer responses on TikTok. The study contributes to the growing literature on social commerce and provides practical insights for digital marketers and MSMEs seeking sustainable E-commerce performance in emerging markets.